Best manufacturing practices in Malaysian small and medium enterprises - Anuar, Afdiman (2009)
Facing increased competitive pressures due to globalisation and increased quality requirements from their customers, small and medium-sized manufacturers must increase their productivity and their competitiveness in order to survive and prosper. Companies can gain competitiveness by increasing the productivity of manufacturing operation and fulfilling the changing needs of customers and employees. Thus, it is important to identify and analyze the practices that are currently being implemented by the manufacturing companies nowadays. A study was conducted to identify the manufacturing practices of the SMEs in Malaysia. The current level of best manufacturing practices in Malaysian ISO certified SMEs and the relationship between manufacturing practices and performance were investigated. A questionnaire-based survey was conducted on 270 ISO9000 certified manufacturing SMEs. Based on an extensive search of literature on performance requirements, eight areas were identified. Thus, the questionnaire was designed consisting of the eight areas which are management, human resources development, technology and product innovation, marketing strategy, quality, production process, supply chain management, and customer focus. A total of 60 respondents were received at 22.2% response rate. Based on a 5-Likert scale which indicate best practices, the results showed that among the eight areas, customer focus is the most important area with the highest mean of 4.16, followed by quality (3.92), management (3.78), supply chain management (3.56), human resource development (3.27), marketing strategy (3.05), production process (3.02), and technology and product innovation with a score of 2.95. The results showed that level of best manufacturing practices can be improved further especially in the area of technology and product innovation. Pearson correlation and stepwise regression were used to test the hypotheses that have been developed. The Pearson correlation results indicated that almost all the benchmarking areas and performance were statistically significant. The regression analysis results showed that each of the benchmarking areas were statistically significant with performance. However, based on stepwise regression, the best regression model obtained was Y = – 1.885 +1.065X1 + 0.467X2 – 0.299X3 + 0.282X4 with R2 = 0.853 where X1 = customer focus, X2 = supply chain management, X3 = quality and X4 = marketing strategy. The negative coefficient showed by quality in the regression model suggested that there are confounding effects and other complex relationship exists among the variables. The project has determined the current level of best manufacturing practices in some Malaysian ISO certified Small and Medium Enterprises (SMEs) and identified the areas affecting the companies’ performance. The results can be used by the SMEs to further improve their manufacturing practices in various area.